1980
DOI: 10.1121/1.2004625
|View full text |Cite
|
Sign up to set email alerts
|

Noise dosimeters: on measurement reliability and instrument accuracy

Abstract: Sporadic reports of substantial variations in measurements of exposure noise dose in the workplace performed with contemporary dosimeters have generated concern in the community of users. Measurement differences ranging up to many hundreds of percent have been reported. Differences have been observed when several dosimeters of different makes have been used simultaneously as well as in instances where apparently identical dosimeters have been used. Moreover significant differences have been observed in day to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, calculation of TWA and LA eq8hr at the time that the reviewed studies were conducted (30–40 years ago) was accomplished without the aid of instruments capable of integrated measurements. The authors’ conclusions do not reflect that the over-prediction of hearing loss could have resulted from inaccurate estimates of actual exposure, due to a prediction error from methodological/instrumentation differences (Earshen, 1980, 1994). More recent research has shown that the adequacy of the exchange rate depends on both noise intensity and noise kurtosis (Lataye and Campo, 1996; Davis, Qiu, Hamernik, 2009), and that the accuracy of L eq predictions of hearing loss risk depends upon duration (hours per day), intensity, and type (continuous vs. intermittent) of noise exposure (Hamernik, Qiu, Davis, 2007; Danielson et al., 1991).…”
Section: Methodological Concernsmentioning
confidence: 82%
“…In addition, calculation of TWA and LA eq8hr at the time that the reviewed studies were conducted (30–40 years ago) was accomplished without the aid of instruments capable of integrated measurements. The authors’ conclusions do not reflect that the over-prediction of hearing loss could have resulted from inaccurate estimates of actual exposure, due to a prediction error from methodological/instrumentation differences (Earshen, 1980, 1994). More recent research has shown that the adequacy of the exchange rate depends on both noise intensity and noise kurtosis (Lataye and Campo, 1996; Davis, Qiu, Hamernik, 2009), and that the accuracy of L eq predictions of hearing loss risk depends upon duration (hours per day), intensity, and type (continuous vs. intermittent) of noise exposure (Hamernik, Qiu, Davis, 2007; Danielson et al., 1991).…”
Section: Methodological Concernsmentioning
confidence: 82%
“…However, neither of their cited references (two abstracts by Earshen 1980Earshen , 1994 suggests systematic overestimation of exposure by earlier sound level measurements. We clearly indicated in our paper that hazard estimates for exposures rich in impact or impulse noise might require additional considerations, such as the measurement of kurtosis.…”
Section: Response To Suter and Nioshmentioning
confidence: 79%